Brand equity and credibility sustaining FMCG purchase decisions through the enduring COVID-19 turbulence in Malaysia. - Chan, Tak Jie; Mu, Yu; Raji, Ridwan Adetunji; Sook, Fern Yeo; Mohamad Noor, Salehhuddin Sharipudin (Hong Kong Success Culture Press, 2024)
This empirical study investigates the impact of brand equity and credibility on 140 consumers’ purchase decisions regarding fast-moving consumer goods (FMCG) in Malaysia during the enduring COVID-19 turbulence. Statistical analysis using PLS-SEM demonstrates brand equity and credibility each directly and positively influence purchase decisions. Further, brand credibility significantly mediates the relationship between equity and purchase decisions. As organizations aim to reclaim losses and rebound from lingering pandemic impacts, results signify maintaining branding investments and favorability can restore consumer trust and choices. Findings also advance theoretical understanding of how risk perceptions amplify reliance on brand signals when navigating decisions.